The Manokwari Declaration: Challenges ahead in conserving 70% of Tanah Papua’s forests - Cámara-Leret, Rodrigo; de Fretes, Yance; Scholes, Edwin; Laman, Timothy G.; Roehrdanz, Patrick; Hannah, Lee; McLeod, Jonathan; Fisher, Larry A.; Deverell, Richard; Bramley, Gemma; Utteridge, Timothy; Schuiteman, Andre; Heatubun, Charlie (Forest and Society, 2019)
The Manokwari Declaration is an unprecedented pledge by the governors of Indonesia’s two New Guinea provinces to promote conservation and become SE Asia’s new Costa Rica. This is an exciting, yet challenging endeavour that will require working on many fronts that transcend single disciplines. Because Indonesian New Guinea has the largest expanse of intact forests in SE Asia, large-scale conservation pledges like the Manokwari Declaration will have a global impact on biodiversity conservation and climate change mitigation.